Laparoscopic splenectomy for littoral cell angioma of the spleen: A case report. Issue 11 (March 2019) - Li, Man-Jiang; Zhou, Xuan; Cao, Jing-Yu; Zhu, Cheng-Zhan; Zhou, San-Shun; Zang, Yun-Jin; Wu, Li-Qun
Abstract: Rationale: Littoral cell angioma (LCA) is a rare primary vascular neoplasm of the spleen. It can be benign or malignant. Pathology and immunohistochemistry are the gold standards for the diagnosis of LCA. Therefore, splenectomy is recommended for the purpose of diagnosis and treatment, and subsequent follow-up is necessary. There are limited reports about LCA. Here, we present a case of a female patient with LCA undergoing laparoscopic splenectomy in order to provide clinical experience in LCA treatment. Patient concerns: A 32-year-old female attended the outpatient Department of Hepatobiliary Surgery for follow-up of hepatic hemangiomas. The patient presented with intermittent abdominal distension, which was slightly under no obvious inducement. Diagnosis: Physical examination found no signs of abdominal tenderness and rebound tenderness, and liver and spleen were impalpable. The contrast-enhanced computed tomography (CT) showed multiple space-occupying lesions in the spleen, mottled low-density lesions, multiple hypoattenuating nodules with no contrast enhancement on the arterious phase. Delayed contrast-enhanced helical CT scan displayed incomplete filling of hypodense splenic lesions. Interventions: Given that it was uncertain whether it was a benign or a malignant tumor, a laparoscopic total splenectomy was performed. Outcomes: The final pathological diagnosis was LCA. Her postsurgical course was uneventful, and no surgery-related complications were found. No signs of recurrence were observed in the 16 months after the operation. Lessons: LCA was a rare primary vascular neoplasm of the spleen, and laparoscopic splenectomy for LCA was safe and feasible, and postoperative course was uneventful. However, regular follow-up and long-time monitoring after splenectomy for LCA is recommended because of its potential malignant biological behavior.